No Cases of PANDAS on Follow-Up of Patients Referred to a Pediatric Movement Disorders Clinic - Kilbertus, Sarah; Brannan, Renee; Sell, Erick; Doja, Asif (Frontiers in Pediatrics, 2014)
Introduction: Pediatric autoimmune disorders associated with streptococcal infection (PANDAS) remains a controversial diagnosis and it is unclear how frequently it is encountered in clinical practice. Our study aimed to determine how many children with acute onset tics and/or OCD met criteria for PANDAS. Materials and Methods: A retrospective review was performed on 39 children who presented to a movement disorders clinic with acute onset tics or OCD from 2005-2012. Results: Out of 284 patients seen over the course of 7 years, only 39 had acute onset tics and/or OCD symptoms. None of the 39 children who presented to us acutely met full criteria for PANDAS. 38% had no association between their symptoms and a group A beta-hemolytic streptococcal infection, while 54% had prior inconclusive laboratory testing done and no prospective exacerbations during the course of the study. Only 8% of patients prospectively had acute exacerbations, however prospective testing for GAHBS in these patients was negative. Discussion: Our results support the notion that PANDAS, if it exists, is an exceedingly rare diagnosis encountered in a pediatric movement disorder clinic. While none of our patients met criteria for PANDAS, two with acute onset OCD would have met criteria for pediatric acute-onset neuropsychiatric syndrome (PANS) indicating that PANS may be a more appropriate diagnosis.